The practice of patient blood management among South African anaesthetic providers - Eddey, Creaghan (University of the Witwatersrand, Johannesburg, 2024)
Patient Blood Management (PBM) is a multidisciplinary and evidence-based approach aimed at optimising patient outcomes by effectively managing and preserving a patient's own blood, minimising unnecessary transfusions, and promoting overall blood conservation strategies. Thus far, perioperative PBM practices of South African anaesthetic providers have not been described. Methods This study prospectively evaluated perioperative PBM practices in South Africa utilising an online survey. In addition, we described the extent to which practices align to the national guidelines, the 2020 South African Society of Anaesthesiologists (SASA) guidelines, and 2014 South African National Blood Service (SANBS) guidelines. Results The information letter was opened 573 times. We received 403 surveys that were more than 50% complete and were included in this study. Most respondents were specialists (54.6%) or specialist trainees (25.1%) within their first five years of practice (54.6%). Most providers (89.3%) often or always record a preoperative haemoglobin. Only 1% of providers would defer elective surgery, other than caesarean section, if the haemoglobin (Hb) was <13 g/dL. Appropriate treatment of preoperative anaemia was rarely or never seen by 65.5% of respondents. Access to point of care (POC) coagulation testing was good with only 25.6% having no access to any POC test. Freeze-dried plasma (FDP) is commonly (89.3%) accepted as a substitute for fresh frozen plasma (FFP). A majority (63.9%) of respondents use a transfusion threshold of 57 g/dL for red cell concentrates (RCC) in non-cardiac patients. Few respondents often or always use cell salvage in non-obstetric surgery where >500 ml of blood loss is anticipated (21.2%), or in obstetric major haemorrhage (21.2%). In major haemorrhage, most respondents often or always monitor for, treat, and prevent hypothermia (97.5%), acidosis (96.0%), hypocalcaemia (90.0%), and hyperkalaemia (91.6%). Tranexamic acid is often or always used commonly in severe trauma (70.7%) and major obstetric haemorrhage (72.1%). Conclusions Overall, PBM practices were poor, and not in keeping with South African guidelines. The management of preoperative anaemia stands out as the most notable deficiency. Key points: Research question: What are the perioperative patient blood management (PBM) practices among South African anaesthetic providers? How do these practices align with the SASA and SANBS guidelines? Findings: Overall, PBM practices were poor, and not in keeping with South African guidelines. Meaning: Important context is provided for PBM in low- and middle-income countries
A research report submitted to the Faculty of Health Sciences, in the partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology , School of Medicine, University of the Witwatersrand, Johannesburg, 2024
Keywords: Patient blood management; Transfusion; Low- and middle-income countries; Blood products; UCTD; SDG-3: Good health and well-being